2011
DOI: 10.1016/j.atmosenv.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particulate matter emission from open burning of rice straw

Abstract: Emission from field burning of crop residue, a common practice in many parts of the world today, has potential effects on air quality, atmosphere and climate. This study provides a comprehensive size and compositional characterization of particulate matter (PM) emission from rice straw (RS) burning using both in situ experiments (11 spread field burning) and laboratory hood experiments (3 pile and 6 spread burning) that were conducted during 2003–2006 in Thailand. The carbon balance and emission ratio method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(74 citation statements)
references
References 35 publications
4
63
1
2
Order By: Relevance
“…Several studies of PM 10 sources in northern Thailand have been reported (Kim Oanh et al, 2011;Phoothiwut and Junyapoon, 2013), but they have focused on the rice straw burning season that occurs in December/January after the rice harvest every year, in contrast to the smoke/haze during the dry season burning in February to March studied here. To the best of our knowledge, our study is the first of its kind to identify the types of plants that were burnt and contributed to airborne PM 10 in the Chiang Mai -Lamphun Basin during the smoke/haze season.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of PM 10 sources in northern Thailand have been reported (Kim Oanh et al, 2011;Phoothiwut and Junyapoon, 2013), but they have focused on the rice straw burning season that occurs in December/January after the rice harvest every year, in contrast to the smoke/haze during the dry season burning in February to March studied here. To the best of our knowledge, our study is the first of its kind to identify the types of plants that were burnt and contributed to airborne PM 10 in the Chiang Mai -Lamphun Basin during the smoke/haze season.…”
Section: Discussionmentioning
confidence: 99%
“…Niemi (2007) compared various datasets for all open biomass sources and developed the first global activity set for the RAINS model drawing on EDGAR3.2FT2000 (Van Aardenne et al, 2005), which we have further extended and updated to accommodate other data sources, allowing gaps to be filled for several countries. Specifically, we have used estimates from the global studies , a number of regional estimates (Cao et al, 2008;Oanh et al, 2011;Pettus, 2009), reporting of emissions to EMEP (http://www. ceip.at), and bilateral discussions within the revision of the European air pollution policy .…”
Section: Agricultural Waste Burningmentioning
confidence: 99%
“…The soot group, contributed about 5-8% of the PM 2.5 mass in all seasons, indicated the contribution from incomplete combustion which in turn would be associated with diesel vehicles and also biomass burning (cooking and open burning) in the study area. The BC fraction in diesel exhaust PM could be as high as 68% (Kim Oanh et al, 2010a) as compared to that in the PM of biomass burning smoke, e.g., about 6% for rice straw burning (Kim Oanh et al, 2010b). However, diesel powered vehicles were only occasionally observed on the local roads while biomass burning (for cooking and open burning of crop residue and solid waste) was routine activities by the local community.…”
Section: Source Contribution Reconstructed Massmentioning
confidence: 99%